O local e o global no funk brasileiro e no kuduro angolano - Faria, Debora Costa de [UNIFESP] (2014)
This work sets out to investigate how musical manifestations considered popular and peripheral, reach ? not without some symbolic negotiation -, spaces outside the contexts in which they are first produced. Taking as reference Angolan kuduro and Brazilian funk, we attempt to understand how global cultural flows influence and are appropriate for local cultural productions, by adding new features and giving new meanings to these references. Besides, the work will investigate the possibilities of production and consumption of these musical genres in places outside of their context of origin. All of this has been done by taking into consideration the contextual and historical differences between Brazilian funk and Angolan kuduro. On the other hand, we are finding that the emergence of both genres of music and dance, outside their own countries, have been considered within a larger phenomenon in which electronic musics produced in the outskirts of large cities are very valued by foreign DJs and producers who spread these types of musics all over the world.